Caracterización de la diversidad y distribución herpetofaunística en la parroquia Guasaganda, sector Machay en el cantón La Maná, provincia de Cotopaxi, periodo 2022. - Guanotuña Guamangate, María Janeth (2022)
The recognized importance of reptile fauna in sectors close to reserves has taken an evolutionary turn for what has been suggested in the present investigation, in the Malqui Machay sector, a place where it has not received much attention from studies of this type of amphibian and reptile components of the region over the years. This study has a larger sampling effort to characterize the richness of this species of fauna in the Piedmont evergreen forest with the aim of evaluating the characteristics presented by the research process, the abundance and distribution of local herpetology and information about the current conservation status of the species. The results collected in June and August varied due to the bioclimate displayed in the two field trips, the wet and dry season. The results collected in June and August varied due to the bioclimate displayed in the two field trips, the wet and dry season. The evaluation obtained is of a pioneering nature based on qualitative and quantitative methods of investigation, and it was evaluated along an ascending gradient from 300 to 1300 m3. The results obtained showed a total record of 8 families and 44 individuals of total sample diversity, as a result of 5 days of active field work in the Malqui-Machay bioclimatic region located within the Hugshatambo and Quinindé river basins, respectively. Species appeared most often 45 minutes from the ruins of Malqui - Machay. The most abundant amphibians were (Epipedobates darwinwallacei) and (Atelopus different). Two threatened species of amphibians of the family (Craugastoridae and Plethodontidae) have been reported according to (PUCE, Biogeographical Diversity, 2021). The reptile observed is (Anolis Gracilipes), a species found while road elevations have increased relatively, and this information dates back to Malqui-Machay in a very important area for the conservation of southwestern Ecuador's remains of the Western Piemontane Evergreen Forest, which has the lentil floodplain area Dominated by shrubs and overlapping areas.